Effect of architectural adjustments on pedestrian flow at bottleneck - Wang, Jianyu; Ma, Jian; Lin, Peng (Collective Dynamics, 2020)
In the last decades, a series of terrible accidents happened within pedestrian crowds, which makes crowd dynamic a significant issue to be investigated. Literature reviews show that pedestrian flow presents different features within different architectural layout. In this paper, pedestrian movement properties at bottleneck are studied by carrying out series of experiments under laboratory condition. The influence of door sizes and exit locations on pedestrian crowd flow is investigated. It was found that larger door width resulted in shorter evacuation time and faster flow rate. By comparing the fundamental diagram among crowd evacuation, the average velocity increases as the width increases under the same density condition. Interestingly, the influence of the boundary layer, as well as the effective width on pedestrian crowd dynamic, was clearly observed. Our results suggest that the combination of exit width and location resulted in a synergistic effect, but the exit widths gradually became the most important factor influencing the flow rate.